Defining and measuring policy coherence for food system transformation: A scoping review - Dewi, Deviana; Aytekin, Destan; Schneider, Kate R.; Covic, Namukolo; Fanzo, Jessica; Nordhagen, Stella; Resnick, Danielle (Elsevier, 2024)
Changes in food systems—across multiple sectors and through all levels of government—are essential for meeting many of the Sustainable Development Goals (SDGs) and other global environmental and health targets. Steering food systems towards common outcomes and ensuring that actions in one area do not undermine progress in another requires policy coherence. This scoping review examines how policy coherence has been broadly defined and measured in areas related to food system transformation to inform conceptualization, definition, and measurement specific to food systems transformation and provide insights for policy and program implementation. We reviewed literature published from January 2000 to December 2022 and identified 47 studies meeting the inclusion criteria. Results show that common features of definitions of policy coherence relevant for food systems are: an emphasis on minimizing tradeoffs and maximizing synergies; policy integration within different areas of government and food systems or across scales (horizontal or vertical coherence); alignment of objectives, interventions, and indicators within a given policy area; and complementarity and consistency of actions and goals within or across sectors of food systems. Measurement methods to date are mainly limited to qualitative policy document review and participatory assessment, with no examples of application at scale. This paper provides a first step towards a definition and measurement approach for policy coherence that can fill this important data gap in monitoring the governance of food systems transformation and synthesizes evidence to guide actions towards greater policy coherence in governing national food systems.